Integrating Artificial Intelligence to Build Character through Islamic Learning in Elementary Schools - Zakariya, Muhammad; Mas’ud; Mustajab; Muhith, Abd (ATTA`DIB, 2025)
This study examines the integration of Artificial Intelligence (AI) in learning Islamic Religious Education (PAI) for character building of elementary school students. This study is motivated by the gap between the ideal condition (das sollen) of integrating AI technology in Islamic character building and the reality in the field (das sein) which is still dominated by conventional methods. Using a qualitative approach with a library research method, this study analyzes primary and secondary sources published between 2019-2024 from various scientific databases such as Scopus, Web of Science, and Sinta 1-3. The results show that the integration of AI in PAI learning has a transformative impact, with an increase in student learning motivation and understanding of religious concepts. The developed AI-based adaptive learning model consists of four main components: Islamic Values Integration System (IVIS), Personalized Learning Pathway Generator (PLPG), Character Development Monitoring System (CDMS), and Interactive Feedback Mechanism (IFM). Factors influencing successful implementation include teacher competence (very high influence), technological infrastructure, institutional support, and learning content suitability (high influence). The implementation strategy is developed in three phases: foundation building, phased implementation, and continuous evaluation. This research contributes to the development of an effective Islamic learning methodology by integrating Islamic values and modern technology, and provides a practical framework for educational institutions in implementing AI for Islamic character building of elementary school students.